Efektivitas Pemanfaatan Media Quizziz sebagai Alat Evaluasi dalam Pembelajaran Ilmu Alamiah Dasar - Rina Novianty (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2026)
This study aimed to analyze the effectiveness of using Quizizz as an evaluation tool in Basic Natural Science learning. The study employed a quantitative descriptive method with a survey approach. The participants consisted of 30 university students who had used Quizizz in the learning process. Data were collected through a Google Form-based questionnaire consisting of closed-ended and open-ended questions, and were analyzed using descriptive statistics and thematic analysis. The results showed that the use of Quizizz received positive responses from students, particularly in terms of enjoyment, ease of use, and attractiveness of the evaluation process. Quizizz was also proven to enhance learning interest, student engagement, and create a more interactive and efficient evaluation process. Features such as randomized questions, time limits, and instant feedback were identified as the main advantages in supporting learning evaluation. However, the effectiveness of Quizizz was still influenced by internet connectivity issues, technical problems, and the potential for academic dishonesty when evaluations were conducted without supervision. It can be concluded that Quizizz is appropriate to be used as an alternative evaluation medium in Basic Natural Science learning, provided that adequate infrastructure and proper planning are available.   Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan Quizizz sebagai alat evaluasi dalam pembelajaran Ilmu Alamiah Dasar. Penelitian menggunakan metode deskriptif kuantitatif dengan pendekatan survei. Subjek penelitian berjumlah 30 mahasiswa yang telah menggunakan Quizizz dalam proses pembelajaran. Data dikumpulkan melalui kuesioner berbasis Google Form yang terdiri atas pertanyaan tertutup dan terbuka, kemudian dianalisis menggunakan statistik deskriptif dan analisis tematik. Hasil penelitian menunjukkan bahwa penggunaan Quizizz memperoleh respons positif dari mahasiswa, terutama pada aspek kesenangan, kemudahan, dan daya tarik evaluasi. Quizizz juga terbukti mampu meningkatkan minat belajar, keterlibatan, serta menciptakan proses evaluasi yang lebih interaktif dan efisien. Fitur pengacakan soal, batasan waktu, dan umpan balik langsung menjadi keunggulan utama dalam mendukung evaluasi pembelajaran. Namun demikian, efektivitas penggunaan Quizizz masih dipengaruhi oleh kendala jaringan internet, gangguan teknis, dan potensi kecurangan apabila evaluasi dilakukan tanpa pengawasan. Disimpulkan bahwa Quizizz layak digunakan sebagai alternatif media evaluasi dalam pembelajaran Ilmu Alamiah Dasar dengan dukungan infrastruktur dan perencanaan yang baik.